Performance of a Brazilian population in the EC 301 calculation and number processing battery: a pilot study Desempenho da população brasileira no processamento numérico e de cálculo através da bateria EC 301: estudo piloto - Gabriela De Luccia; Karin Zazo Ortiz (Arquivos de Neuro-Psiquiatria)
BACKGROUND: From a neuropsychological point of view calculation is a very complex function. A simple arithmetic operation demands many neurocognitive mechanisms that involve verbal, spatial and graphical processing, memory and attention. OBJECTIVE: To verify the calculation and number processing of healthy subjects and the effect of gender, age and schooling on their performance. METHOD: Forty-four normal subjects without complaints or neurological changes were evaluated. RESULTS: The educational level was significantly linked to performance in the majority of tests of the EC 301 battery, whereas no differences were noted regarding age and gender. CONCLUSION: Evaluation of the data of the healthy population shown in this study indicated that educational level can affect calculation and number processing, It is possible to note that battery EC 301 demonstrated sensitivity for appraisal of these abilities and therefore can be employed for clinical assessment in calculation and number disorders. INTRODUÇÃO: O cálculo do ponto de vista neuropsicológico é uma função muito complexa. Em uma simples operação aritmética estão envolvidos diversos processos neurocognitivos que envolvem os processamentos verbais, espaciais, gráficos, atenção e memória. OBJETIVO: Este estudo teve por objetivo verificar o desempenho de indivíduos saudáveis, no processamento numérico e de cálculo, através da bateria EC 301 e verificar as interferências do sexo, da idade e da escolaridade no desempenho destes indivíduos. MÉTODO: Foram avaliados 44 sujeitos normais sem queixas e/ou alterações neurológicas. RESULTADOS: O nível educacional mostrou-se fortemente relacionado ao desempenho obtido na maioria das provas da bateria EC 301, enquanto em relação ao sexo e idade não foram encontradas diferenças. CONCLUSÃO: Os dados encontrados na população avaliada neste estudo mostraram que o nível educacional pode influenciar o desempenho do processamento numérico e de cálculo, sendo possível observar que a bateria EC 301 mostrou-se sensível para avaliar estas habilidades, podendo assim ser utilizada na avaliação clínica dos distúrbios numéricos e de cálculo.